Helicobacter pylori serologic status has no influence on the association between fucosyltransferase 2 polymorphism (FUT2 461 G/A) and vitamin B-12 in Europe and West Africa - Oussalah, Abderrahim; Besseau, Cyril; Chery, Céline; Jeannesson, Elise; Guéant-Rodriguez, Rosa-Maria; Anello, Guido; AVOGBE, PATRICE HODONOU (My University, 2012)
Background: Genomewide association studies have shown a rela- tion between plasma vitamin B-12 concentration and the 461G/A polymorphism of fucosyltransferase 2 (FUT2), a gene associated with susceptibility to Helicobacter pylori infection. Objective: We evaluated in 2 populations the association of FUT2 461 G/A polymorphism with vitamin B-12 and related metabolic markers and investigated whether the influence of FUT2 on H. pylori serology is part of the mechanisms that underlie these associations. Design: The study included 1282 ambulatory subjects from Europe and West Africa. Blood concentrations of vitamin B-12, folate, homocysteine, and methylmalonic acid were measured. Genotyping was performed by real-time polymerase chain reaction. H. pylori serology testing was performed by using ELISA. Results: In univariate analysis, FUT2 461 A/A genotype was asso- ciated with higher plasma vitamin B-12 concentration in the total population (P = 0.0007) as well as in Europe (P = 0.0009) and in West Africa (P = 0.0015). Positivity for H. pylori serology was higher in West Africa (P , 0.0001) and was not associated with low plasma vitamin B-12. The prevalence of H. pylori–positive patients did not differ among FUT2 461 G/A genotypes (P = 0.2068). In multivariate analysis, FUT2 461 G/A genotype (P = 0.0008), but not positive H. pylori serology, was an independent predictor of plasma vitamin B-12 concentration. Conclusion: This study confirms the influence of FUT2 461 G/A polymorphism on plasma vitamin B-12 concentration and showed no influence of H. pylori serologic status on this association in ambulatory subjects from Europe and West Africa.